Load frequency control of power systems with Sugeno fuzzy gain scheduling PID controller - Hassan, L.H.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2009)
This paper proposes a new Fuzzy Gain Scheduled Proportional, Integral and Derivative (FGPID) controller by using Takagi-Sugeno (TS) fuzzy system to the load frequency control problem in multi-area power systems. The TS fuzzy inference engine is chosen and the range of the controller is selected suitably to enhance the output performance of the system. Simulation results demonstrate the ability of the proposed control model in damping the frequency oscillations and tie line power deviations due to area load changes. The approach is compared against two controllers in the literature; Fuzzy Gain Scheduling Integral and Derivative (FGID) controller, and Fuzzy Gain Scheduling Proportional and Integral (FGPI) controller. Settling times, overshoots, undershoots and Integral Square Error (ISE) of frequency deviation are used as comparison criteria. Nonlinear simulation results show that the proposed controller provides better performance than the other two models.